Application of Orthopedic Robot in the Diagnosis and Treatment of Femoral Neck Fracture - Xue, Wuxin; Awang, Zarina (Journal of Theory and Practice in Engineering and Technology, 2025)
Digital orthopedics is an emerging interdisciplinary field that incorporates advanced digital technologies into orthopedic clinical practice. This field leverages digital processing, imaging technologies, and computational power to address both fundamental and clinical challenges in orthopedics. Recent advancements have expanded the scope of digital orthopedics to include robotic-assisted surgeries, computer-assisted navigation, virtual and augmented reality, 3D printing, finite element analysis, remote surgical interventions, and artificial intelligence applications. This paper explores the application of these technologies, with a particular focus on orthopedic robotic systems in the diagnosis and treatment of femoral neck fractures, highlighting their impact on surgical precision and patient outcomes.